RSV Disease Threat and Innovative Prevention Methods in Health Protection: A Review - Dąbrowska, Paulina; Żuber, Michał; Bochyński, Karol; Molenda, Katarzyna; Ciuba, Katarzyna; Borodziuk, Barbara; Borodziuk, Filip; Dacka, Michał; Giżewska, Kamila; Białogłowski, Konrad (Journal of Education, Health and Sport, 2024)
Respiratory syncytial virus (RSV) causes infections of the lower respiratory tract. A group particularly vulnerable to severe infection are young children under 2 years of age and the elderly. The infection can cause the entire spectrum of respiratory symptoms from upper respiratory tract infections to severe courses requiring assisted breathing. Until recently, the only form of protection against infection was passive immunization, i.e. administration of immunoglobulins. Chief among these are palivizumab and nirsevimab. In May u June 2023, the Food and Drug Administration (FDA) approved for use 2 vaccines against RSV are Arexvy and Abrysvo. In this study, we focus on presenting and describing the clinical evidence supporting the effectiveness of these immunization methods.